2010
DOI: 10.1038/cddis.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc supplementation of 3xTg-AD mice increases BDNF levels and prevents cognitive deficits as well as mitochondrial dysfunction

Abstract: The overall effect of brain zinc (Zn2+) in the progression and development of Alzheimer's disease (AD) is still not completely understood. Although an excess of Zn2+ can exacerbate the pathological features of AD, a deficit of Zn2+ intake has also been shown to increase the volume of amyloid plaques in AD transgenic mice. In this study, we investigated the effect of dietary Zn2+ supplementation (30 p.p.m.) in a transgenic mouse model of AD, the 3xTg-AD, that expresses both β amyloid (Aβ)- and tau-dependent pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 39 publications
6
123
2
1
Order By: Relevance
“…Conversely, Zn 2+ supplementation for 3 x TG-AD transgenic mice actually attenuated disease pathology [27]. In support of this mice depleted of synaptic Zn 2+ through a ZnT3 knockout mutation present agedependent memory impairments similar to those observed in Alzheimer's disease models [28]; this is particularly significant as the authors found that ZnT3 levels decline in humans with aging, particularly those with Alzheimer's disease [29].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Conversely, Zn 2+ supplementation for 3 x TG-AD transgenic mice actually attenuated disease pathology [27]. In support of this mice depleted of synaptic Zn 2+ through a ZnT3 knockout mutation present agedependent memory impairments similar to those observed in Alzheimer's disease models [28]; this is particularly significant as the authors found that ZnT3 levels decline in humans with aging, particularly those with Alzheimer's disease [29].…”
Section: Introductionmentioning
confidence: 90%
“…Alzheimer's like symptoms in animal studies [24,25,27,29], as not only is Aβ misfolding extremely sensitive to Zn 2+ , but also to the ratio of Aβ and Zn 2+ as well as its interplay with Cu 2+ . It has recently been shown that physiologically relevant N-terminally truncated forms of A have a femto-molar affinity for Cu 2+ [70], it remains to be established what impact Zn 2+ might have on these very tightly bound Cu 2+ complexes.…”
Section: Contrasting and Dominating Influence Of Zn 2+ Over Cu 2+ In mentioning
confidence: 98%
“…Furthermore, post hoc analysis revealed a statistically significant reduction of cognitive decline on two tests (and nearly significant for the MMSE) when analyses were limited to the twenty-nine patients over seventy years old (Brewer 2012). Furthermore, dietary zinc deficiency exacerbated behavioral and histological pathology in an APP mutant mouse (Stoltenberg et al 2007), and zinc supplementation prevented AD pathology in the 3X-Tg mouse model (Corona et al 2010). However, another study found impaired memory performance in zinc supplemented APP mutant mice associated with decreased Ab deposition (Linkous et al 2009).…”
Section: Therapies Aimed At Modulating Zinc Availabilitymentioning
confidence: 96%
“…Levels of BDNF and NGF have been shown to decrease in zinc(II) deficient mice [125], hence zinc(II) dietary supplementation seems to replenish the NGF [126], as well as the BDNF, level [127]. Moreover, chronic treatments with zinc(II) ion induced a BDNF mRNA upregulation in the cortex and hippocampus [128], strongly suggesting a more direct role of this metal ion in the neurotrophins expression.…”
Section: Metals and Neurotrophinsmentioning
confidence: 96%